Physicochemical Parameters and Purification of Pulp Effluent (Black Liquor) - Oluwatosin Shokunbi; R.O Omenka (Journal of Tropical Pharmacy and Chemistry, 2022)
Pulp and paper Industry poses a great significant problem in Environmental pollution and they consume high energy, water and resources. The present study was undertaken to purify pulp effluent (black liquor) using sand bed filters and adsorption method (Activated Carbon). The physicochemical parameters carried out were pH, colour, temperature, turbidity, total alkalinity (TA), total hardness (TH), chemical oxygen demand (COD), total suspended solids (TSS), total solids (TS) and total dissolved solids (TDS) using standard methods by American Public Health Association (APHA). The results obtained for black liquor and treated effluent were; colour (dark brown), pH (11.59 & 9.14), temperature (31 & 30 ), turbidity (1.78 &0.77 NTU), TA (10,000mg/L & 300mg/L), TH (325 mg/L & 220 mg/L), COD (2663 mg/L & 174.85 mg/L), TSS (0.09 mg/L & 0.00 mg/L), TS (0.9 mg/L & 0.17 mg/L), TDS (1354 mg/L) respectively. Highly significant differences were found between the effluent and treated water. The results indicated that pulp and paper Industrial effluents are highly polluted and can be toxic or harmful to human beings when released into water bodies without being treated.